IMPACT OF COVID-19 ON THE CAPITAL MANAGEMENT (IMPLEMENTATION AND COMPLIANCE OF THE BASEL-3 FRAMEWORK) OF THE BANKS IN BANGLADESH - Hasan, K. B. M. Rajibul; Pareek, Gagan (Asian Finance & Banking Review, 2022)
The global economic condition has faced tremendous pressure due to the arrival of Covid-19. Covid-19 has affected the business and financial system severely and put extra pressure on banks in earnings, expenses, and operating efficiencies. Capital management has been a challenge for the banks in Bangladesh due to higher NPLs ratio, poor governance, and weakness in the quality of assets. The Covid situation has deepened manifold due to regulatory changes, fall in earnings, and asset quality with extra facilities being offered to the borrowers during the crisis period. This paper investigates the impact/s of Covid-19 on capital requirements, capital adequacy ratio, and capital management of banks in Bangladesh. The paper analyzes the effects of Covid-19 on key risk factors of the banking sector i.e. capital requirements and financial stability. The study is based on time series data comprising 62 banks operating in Bangladesh and a total of bank-year observations over the period 2012 to 2021. The empirical output of the paper unveils the degree of changes in capital adequacy of banks in the post-Covid situation. The paper also illustrates the impact of Covid-19 on CAR due to changes in performance indicators represented by different financial ratios- ROA, NIM & ROE which have been affected negatively in the post-Covid situation due to the effects of regulatory changes during the Pandemic. Although Classification status was not changed due to regulatory relaxation, the expenses on provisions and others increased substantially and resulting in a fall in profits and affecting the CAR negatively. The findings also show that there exists interconnectivity between the performance indicators and capital management. JEL Classification Codes: D24, G32, G21.